Cross-speaker variation in voice source correlates of focus and deaccentuation - YANUSHEVSKAYA, IRENA; GOBL, CHRISTER; NI CHASAIDE, AILBHE (My University, 2017)
This paper describes cross-speaker variation in the voice source correlates of focal accentuation and deaccentuation. A set of utterances with varied narrow focus placement as well as broad focus and deaccented renditions were produced by six speakers of English. These were manually inverse filtered and parameterized on a pulse-by-pulse basis using the LF source model. Z-normalized F0, EE, OQ and RD parameters (selected through correlation and factor analysis) were used to generate speaker specific baseline voice profiles and to explore cross-speaker variation in focal and non-focal (post- and prefocal) syllables. As expected, source parameter values were found to differ in the focal and postfocal portions of the utterance. For four of the six speakers the measures revealed a trend of tenser phonation on the focal syllable (an increase in EE and F0 and typically, a decrease in OQ and RD) as well as increased laxness in the postfocal part of the utterance. For two of the speakers, however, the measurements showed a different trend. These speakers had very high F0 and often high EE on the focal accent. In these cases, RD and OQ values tended to be raised rather than lowered. The possible reasons for these differences are discussed.
INTERSPEECH 2017
Keywords: Voice source; Focus; Accentuation; Deaccentuation; Cross-speaker variation; Digital Humanities